Model of Coal Terminal Location in the Collaborative Supply Chain of Coal-Fired Power Plants Considering Transportation Modes and Blending - Febrina, Winda; Puspa Kenaka, Saskia; Suprayogi (ITB Graduate School Conference, 2025)
This research aims to identify the optimal placement of coal terminals within a collaborative coal supply chain network for large-scale coal-fired power plants (CFPPs) in Indonesia, aiming to enhance overall supply chain efficiency. A mathematical optimization framework is developed, incorporating key factors such as benchmark coal prices, selection of maritime transport modes, infrastructure development of coal terminals, blending requirements based on calorific value (GCV), and the balance between supply and demand capacities. The study utilizes data sourced from various coal producers, CFPPs as demand centers, and regulatory guidelines issued by the Directorate General of Mineral and Coal under the Ministry of Energy and Mineral Resources. Given the diversity of GCV specifications and vessel types typically found in coal logistics operations, the proposed model offers a practical foundation for real-world supply chain optimization. It also functions as a strategic planning tool for tailoring coal distribution to the specific requirements of individual CFPPs.